Oral Supplementation With Butyrate Improves Myocardial Ischemia/Reperfusion Injury via a Gut-Brain Neural Circuit - Yu, Zhiyao; Han, Jiapeng; Chen, Huaqiang; Wang, Yueyi; Zhou, Liping; Wang, Meng; Zhang, Rong; Jin, Xiaoxing; Zhang, Guocheng; Wang, Changyi; Xu, Tianyou; Xie, Mengjie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective Butyrate, a short-chain fatty acid (SCFA) produced by the intestinal microbiota, plays a protective role in cardiovascular diseases (CVDs), but the mechanisms involved in this process remain unelucidated. We aimed to explore the effect of butyrate on myocardial ischemia/reperfusion (I/R) injury through the gut-brain neural circuit. Methods Rats were randomly divided into four groups: sham group (sham), I/R group (I/R), I/R+ butyrate group (butyrate), and I/R+ butyrate+ vagotomy group (vagotomy). The rats were treated with sodium butyrate for 4 weeks, and the gut-brain neural circuit was investigated by subdiaphragmatic vagotomy. Results Butyrate treatment significantly reduced the infarct size and decreased the expression of creatine kinase (CK), creatine kinase myocardial isoenzyme (CK-MB), and lactate dehydrogenase (LDH) compared with the values found for the I/R group. In addition, the I/R-induced increases in inflammation, oxidative stress, and apoptosis were attenuated by butyrate. However, the above-mentioned protective effects were diminished by subdiaphragmatic vagotomy. The RNA sequencing results also revealed that the butyrate-induced protective changes at the cardiac transcription level were reversed by vagotomy. An analysis of the heart rate variability (HRV) and the detection of norepinephrine (NE) showed that butyrate significantly inhibited the I/R-induced autonomic imbalance, but this inhibition was not observed in the vagotomy group. Butyrate treatment also suppressed the neural activity of the paraventricular nucleus (PVN) and superior cervical ganglion (SCG), and both of these effects were lost after vagotomy. Conclusions Butyrate treatment significantly improves myocardial I/R injury via a gut-brain neural circuit, and this cardioprotective effect is likely mediated by suppression of the sympathetic nervous system.